Development of Supramolecular Coordination Materials Using Naphthalimide and 2,6-bis(triazol-4-yl)pyridine Motifs - Lovitt, June Ivy (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
Structural coordination chemistry can be ultilised to develop functional supramolecular materials such as coordination polymers, soft materials, and metal organic frameworks. By applying the principles of self-assembly an understanding can be gained about the underlaying processes directing the generation of such functional materials and how metal ions can fine tune the resulting structure and morphology, thus enabling a method for the prediction of supramolecular architectures. The naphthalimide and 2,6-bis(triazol-4-yl)pyridine motifs are often chosen as structural units in supramolecular coordination chemistry due to the ease of their functionalisation. This thesis, entitled ?Development of supramolecular coordination materials using naphthalimide and 2,6-bis(triazol-4-yl)pyridine motifs? describes the synthesis, characterisation and self-assembly properties of ligands incorporating either the naphthalimide fluorophore or the 2,6-bis(1,2,3-triazol-4-yl)pyridine scaffold as well as their coordination chemistry with d-metal ions. Chapter 1 provides an overview for the recent advances in metallosupramolecular chemistry and approaches in the generation of various functional materials. The most up to date developments of supramolecular architectures using naphthalimide and 2,6-bis(triazol-4-yl)pyridine scaffolds are discussed with particular focus on metal directed self-assembly. It is concluded by highlighting the research explored in the subsequent chapters. Chapter 2 describes the synthesis and characterisation of two N-(2-picolyl) substituted bis-imide ligands. The coordination chemistry with late d-block metal ions in the crystalline and solution states were subsequently explored. The influence of the solvent interactions on the coordination polymer structures was also probed through solvent exchange experiments. Chapter 3 discusses the synthesis and characterisation of two naphthalimide Tr?ger base ligands. The photophysical properties of the ligands were investigated through solvatochromism experiments. One of the ligands was also employed as a potential fluorescence probe for the sensing of structurally assorted antibiotics. The coordination chemistry of the ligand with d-block metal ions through structural characterisation and solvothermal synthesis of two supramolecular coordination polymers was carried out. Finally, the morphological properties of the scaffold were explored. Chapter 4 describes the synthesis of two morpholino-substituted naphthalimide ligands. Their supramolecular properties were studied in the crystalline, solution and gel phases. The stimuli responsive properties of the gels were also investigated. In the solution state, the pH responsiveness properties and counterion influenced aggregation of the ligands was examined. Finally, the microparticle formation over the pH range was probed through various material characterisation techniques. Chapter 5 focuses on the synthesis and characterisation of six 4-(N-alkyl-piperazine)-1,8-naphthalimide ligands. The photophysical properties of the ligand were explored in the solution with particular focus on the interplay between substituent and overall pH response. The supramolecular self-assembly properties were investigated through solvent-mixture studies in the solution state and SEM imaging to study the range of supramolecular architectures present. Chapter 6 discusses the synthesis of three [2]catenane interlocked molecules, using the 2,6-bis(triazol-4-yl)pyridine motif which were structurally characterised in the solid state. The coordination chemistry of the diacid derivatives, open olefin catenane precursors and [2]catenanes was explored in the solid and solution states. The morphological properties of the [2]catenanes were investigated through SEM and showed various self-assembled architectures. Chapter 7 details the synthesis and solid-state analysis of several isostructural metal-organic frameworks using the 1,3,5-cyclohexyltricarboxylic acid as an alternative small molecular building block. For this system the solvent exchange studies were carried out and the gas sorption properties of the frameworks were also examined. Chapter 8 will discuss the final conclusions and future work for the thesis. Chapter 9 outlines the experimental procedures for the work presented. References are presented in Chapter 10. The supplementary data and spectra to support preceding chapters is presented in several Appendices.
APPROVED
Keywords: Supramolecular chemistry; Naphthalimide; Trogers base; Sensing; Spectroscopy; 2,6-bis(triazol-4-yl)pyridine; Self-assembly; catenane; MOFs; Coordination complex